Traumatic childhood events of parents enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC) [version 1; peer review: 2 approved] - Genette Ellis; Yasmin Iles-Caven; Kate Northstone; Jean Golding (Wellcome Open Research, 2020)
Background: Early life experiences can have a significant impact on an individual’s later behaviour, the way they view the world, their beliefs and their success at forming strong interpersonal relationships. These factors may subsequently influence the way that the individual may parent their children, which in turn may have an effect on their child’s behaviour, mental health and world view. Research has linked early traumatic life experiences in the parent’s childhood to disorganised attachment to their own child. In this paper we describe the data collected from parents enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC) on traumatic events experienced during their childhood, so that it can act as a resource for researchers in the future when considering outcomes on the adult, their children and grandchildren. Methods: Data were collected via multiple questionnaires completed by parents enrolled into the ALSPAC study. During pregnancy and post-delivery, questionnaires were administered between 1990 and 1992 via post to the study mothers and their partners. Data were collected on life events including bereavement, sexual abuse, physical abuse, abandonment, neglect, memories of childhood and accidents. Other reports of traumatic events in childhood were reported by parents using free text. This can be made available to researchers for coding on request.